Prestasi dan Kemandirian Belajar dalam Geometri Tranformasi melalui Learning Cycle 5E Berbantuan Software - Pitriani, Pitriani (Universitas Islam Negeri Raden Intan Lampung, 2018)
This action research was aimed at describing the students’ achievement and self-regulated learning after taking the instruction using Software-Assisted Learning Cycle 5E. Learning Cycle 5E are engagement, exploration, explanation, elaboration, and evaluation. The subjects were the students of the Mathematics Education Department of FKIP Universitas Tamansiswa Palembang taking Geometry Transformation Subject in the 2017/2018. The steps of this two-cycle action research included: planning, acting, observing, and reflecting. The prior condition (pre-cycle) showed that the average of students’ achievement is 55.64 with the average student passing is 54,29%. After the application of Reciprocal Teaching, the average of students’ achievement increased to 58,56 in cycle I (60,00%) and to 81,44 (86,67%) in cycle II. Self-regulated learning shows the positive result. The students showed a positive response. The students were enthusiastic about joining the class.